The influences of acculturation strategies on physician trust among internal migrants in Shanghai, China: a cross-sectional study in 2021 - Enhong Dong; Enhong Dong; Yue Yan; Sheng Ji; Jiabin Li; Tingting Wang; Jiahua Shi; Ting Xu; Weimin Gao; Yuping Liu; Shixiang Zhang (Frontiers in Public Health)
PurposeThis study aimed to clarify patterns of Berry’s acculturation strategy and further identify the factors influencing physician trust among internal migrants.MethodsThis study used a sample of 1,200 respondents of Shanghai’s migrant population through an online survey (Wenjuanxing platform) from January 2021 to December 2021. K-means cluster analysis and multivariate logistic regression models were used to identify acculturation strategy patterns of internal migrants and the factors influencing their physician trust in China.ResultsAmong the 1,117 valid respondents, 85.5% were aged 18–39 years, 51.8% (579) were male, 74.8% (836) were married, and 62.9% (703) had completed university or junior college education, 62.1% (690) were covered by urban employee medical insurance, and 46.3% (517) had an annual income of 110,000–250,000 yuan. Through K-means clustering analysis, four clusters of acculturation strategy patterns were obtained: integration, assimilation, separation, and marginalization. When controlling for all significant socioeconomic and other covariates, compared to physician trust of the respondents adopting the separation acculturation strategy groups, the OR values of physician trust of the respondents adopting the integration and assimilation acculturation strategy groups were 1.979 (p < 0.01) and 1.585 (p < 0.01), respectively.ConclusionBerry’s framework delineates four acculturation strategy patterns applicable to internal migrants in Chinese megacities, and the effects of these distinct patterns on trust in physicians have been demonstrated. This research provides valuable insights into the dynamics of doctor-patient relationships among internal migrants in China’s megacities. Therefore, it is advisable for the Chinese government to launch a combined effort from multiple stakeholders to adopt targeted interventions designed for specific demographic groups to foster greater trust in physicians among internal migrants.